Longitudinal assessment of amyloid‐beta deposition in initially amyloid‐negative individuals with [11C]‐PIB PET imaging: Neuroimaging / Optimal neuroimaging measures for early detection. (7th December 2020) - Hatashita, Shizuo; Wakebe, Daichi
Abstract: Background: The earlier stage of amyloid‐beta (Aβ) deposition, before Aβ is widespread throughout cortex, remains poorly understood. The longitudinal change of Aβ deposition was evaluated with [11C]‐PIB PET in initially amyloid‐negative subjects. Method: Sixteen cognitively normal (CN) and 7 mild cognitive impairment (MCI) subjects (age 60‐75 years) who were amyloid‐negative at baseline underwent cognitive assessment and 60‐min dynamic [11C]‐PIB PET at two or more over 5.0 to 9.4 years of a long follow‐up, and apolipoprotein‐E (APOE) genotype assessment. Regions of interest were defined in the bilateral cortex on co‐registered MRI. A quantitative analysis for [11C]‐PIB was used with the distribution value ratio (DVR). Longitudinal changes in PIB DVR values were evaluated in the same regions and an annual rate of change in PIB DVR was calculated. Result: Seven (30.4%) of 23 initially amyloid‐negative subjects converted to be globally amyloid‐positive (global DVR ≥1.40) over a follow‐up of 6.5±1.4 years (converter). A global DVR increased from 1.22±0.07 at baseline to 1.63±0.15 (n=7, p<0.01) at a last follow‐up. In contrast, in the 16 subjects, a global DVR was 1.15±0.07 at baseline and did not change over a follow‐up period (stable). An annual increase of global DVR in converters was 0.057±0.019 per year (n=7, p<0.01), larger than that in stable subjects (0.004 ± 0.013, n=16). An increase of global DVR was not correlated with baseline global DVR (r=0.26, n=23, p=0.22) or baseline age (r=0.15, n=23, p=0.47). Four (66.6%) of 6 APOE ε4 carriers converted to be amyloid‐positive while 3 (17.6%) of 17 APOE ε4 non‐carriers did (Fisher's exact p<0.05). Among cortical regions, regional DVR in the lateral temporal cortex increased to 1.48±0.06 (n=6) above regional positivity threshold over 2.9±1.5 years of a follow‐up and its period was the shortest. Furthermore, an increase of regional DVR prior to reaching the globally positive threshold was 0.084±0.050 per year in the precuneus, which was the largest. Conclusion: Amyloid‐negative individuals, especially with APOE ε4, could convert to be globally amyloid‐positive with extensive cortical spread of Aβ, based on an early Aβ deposition in lateral temporal cortex and a large increase of Aβ deposition in precuneus.